Potential Output in the Seven Major OECD Countries - Torres, Raymond (OECD Economics Department Working Papers, 1989)
This paper outlines the concepts and methods used by the OECD Secretariat to derive estimates of potential output and capacity utilisation for the major seven countries. While there are many alternative definitions of potential output, the one which is currently being used by the OECD Secretariat refers to the level of output that is consistent over the medium-term with stable inflation. The paper also contrasts the OECD approach and estimates with those published recently by the IMF. Finally, it presents the results of some INTERLINK simulations designed to illustrate some of the possible effects of faster productivity and potential output growth on macroeconomic performance ...